DISIPLIN WAKTU GURU MENGAJAR DI MADRASAH IBTIDAIYAH MUHAMMADIYAH SEMANTIR TAHUN PELAJARAN 2023-2024 - Shahrukhan Shahrukhan; Hifza Hifza; Patriana Patriana (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study was to describe: 1) Teachers' time discipline in teaching at MIS Muhammadiyah Semantir in the 2023-2024 Academic Year; 2) What are the obstacles for the principal in disciplining teaching time at MIS Muhammadiyah Semantir in the 2023-2024 Academic Year; 3) Efforts by the principal in overcoming obstacles to disciplining teaching time at MIS Muhammadiyah Semantir in the 2023-2024 Academic Year. This study uses a qualitative approach and a qualitative descriptive research type. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. (1) Teachers' time discipline in teaching at MIS Muhammadiyah Semantir in the 2023-2024 Academic Year are as follows: first, teachers feel bored in teaching, second, lack of teacher assertiveness in obeying regulations, third, lack of responsibility in teaching. (2) The obstacles faced by the head of the madrasah in disciplining teaching time at MIS Muhammadiyah in the Academic Year are as follows: first, the head of the madrasah has not provided a policy on time discipline, second, lack of attention to teacher attendance when coming to the madrasah, third, lack of awareness in disciplining time. (3) The forms of efforts by the head of the madrasah in overcoming obstacles to teaching time discipline at MIS Muhammadiyah Semantir are as follows: first, the head of the madrasah gives verbal warnings to teachers who are late, second, provides coaching and monitoring during meetings.